Cost and acceptability of substituting carabeef for beef in institutional pork and beef main dishes - Uybarreta, Leonor S.
This study was done to determine the effects of substituting varying amounts of carabeef for beef in combination pork and beef main dishes which are served by the UP-Philippine General Hospital to its Dining Hall diners and charity patients on full diet. A control meat proportion which does not contain carabeef and four experimental meat proportions containing increasing quantities of carabeef were tested in the production of Adobo, Piquat, Sinigang,and Tinola. Data on cost (cost of the meats, cost of labor involved in the processing of the meats, and cost of fuel used in cooking the meats), meat cooking time, and meat shrinkage were collected. The acceptability of each dish tested was measured through questionnaires. The qualities of the dish rated included color and appearance, odor, taste, tenderness, portion size and general acceptability. The results of the study showed no significant differences among the 5 meat proportions regarding meat cost, shrinkage, and acceptability. However, the 5 meat proportion were found to vary from each other significantly as regards meat fuel cost, meat labor cost, and meat cooking time.